Application of Discovery Learning Model for Training German Vocabulary Mastery of Students of Class XI IBB SMA Negeri 1 Gondanglegi - Rei Fida Zamzamiyatna; Lilis Afifah (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2022)
This article explains the results of research that aimed to describe the application of the Discovery Learning model to practice students’ mastery of German vocabulary, especially in the “Wohnung” theme and to find out students' responses to the application of this model in learning German.This research used descriptive qualitative method, by which the researcher was the key instrument and the data were gathered using supporting instruments, namely observation sheets and questionnaire sheets. Furthermore, the data sources were 22 students of class XI IBB SMA Negeri 1 Gondanglegi. The results showes that the application of Discovery Learning  model to train students' German vocabulary mastery worked successfully as planned.  In addition, this learning model is able to make students think critically, creatively, collaboratively, and more actively during learning process.  According to the students, this model is pleasurable because it makes them more motivated to learn German. Finally, they think that this model allows them to remember vocabulary related to the “Wohnung” theme easier.